Desenvolvimento sustentável e desigualdade regional nas microrregiões do Paraná - Rodrigues, Katia Fabiane (2015)
This thesis aimed to investigate the process of sustainable development in micro Paraná, through the development of aggregate indices for the years 2000 and 2010. In addition, we sought to understand how the variables that determine development are distributed among the micro-regions and how they affect the issue of regional inequality. To envision this scenario, some theoretical elements were drawn between them, pointing to understanding and context of the theory of economic development, environmental currents and the concept of eco-development / sustainable development. This theoretical route, it is important to understand the fundamentals of design and evolution of the concept of development, considering its dynamic character. Considering the need to measure development, linked to what was postulated by Agenda 21, the present study sought to point out some methods, including the Human Development Index - HDI, the model Pressure-State-Response and its derivations, the Footprint Ecological, the Barometer of Sustainability and the Sustainability Panel. That said, to meet the research objectives, first was given a group of indicators, then made up some indexes, which were divided into twelve sub-indices within the four dimensions of sustainable development, social, environmental, economic and institutional. Finally, to clarify the issue of regional differences, and the results found in the analysis of the indices used if the coefficient of variation weighted Williamson, to understand how the microregions are unequal, considering the indicators that reflect the development. On that basis, it was found that the most developed micro-regions were those that the period showed a solid economic structure, which led to improvements in income, employment and infrastructure. Otherwise, the less developed micro-regions showed some limitations, income, employment, sanitary conditions and institutional structure. Among the micro more and less developed state, there was a major contradiction, ie the most developed micro presented elements that impact the environment and a high level of violence, to the point that the least developed micro-regions, impact unless the middle environment and have fewer factors that shape an insecure setting. Thus, it became clear that the economic dimension strong influence in the development process of the state's micro-regions, thereby revealing that the micro do not have a harmony between the different sustainabilities. In addition to these elements, it was also examined the presence of strong regional differences in twenty-one indicators measuring sustainable development.